Shear behavior of concrete beam reinforced in shear with carbon fiber-reinforced polymer mesh fabric (CFRP-MF) configuration. (1st September 2020) - Li, Weiwen; Tang, Shiying; Huang, Zeqi; Yang, Xu; Shi, Tiansheng; Xing, Feng
Highlights: Shear behavior of concrete beams shear reinforced by CFRP-MF. Analysis of concrete beams shear reinforced by CFRP-MF. Predictions of the specimens' shear strength by shear design provisions and FEM. Abstract: The paper proposes a new type of fiber-reinforced polymer (FRP) shear reinforcements for reinforced concrete (RC) beams. The specimens are shear reinforced with carbon fiber-reinforced polymer mesh fabric (CFRP-MF) configuration rather than traditional steel stirrups. The shear behaviors of the 15 concrete beams reinforced in shear with CFRP-MF configuration or with/without steel stirrups (as control specimens) was investigated in this paper. The variables of the investigation include shear span-depth ratio ( a / d = 1.0, 2.5 and 3.5) and the shear reinforcement ratio of CFRP-MF composites (0.036%, 0.067% and 0.097%). The experimental results indicate that the concrete beams reinforced in shear with the CFRP-MF configuration have similar shear behaviors to the corresponding RC control beams reinforced in shear with steel stirrups especially in overall load-deflection relationship, shear strength, and the crack pattern of ultimate state. The predictions of the specimens' shear strength by using shear design provisions in ACI 440.1R-15, CSA S6-14 and CSA S806-12 are examined and compared.